An approximation to surface admittance of Y-rotated langasite - DANICKI, E. (Archives of Acoustics, 1995)
New piezoelectric crystal, langasite, is expected to rind many applications in piezoelectronics. An approximation to its electro-mechanical surface property is given that allows to analyze B-G waves in the crystal and corresponding SAW devices.